2019
DOI: 10.3389/fncel.2019.00397
|View full text |Cite
|
Sign up to set email alerts
|

Post Stroke Seizures and Epilepsy: From Proteases to Maladaptive Plasticity

Abstract: Post stroke epilepsy (PSE) is the most common cause of seizures in the elderly, yet its underlying mechanism is poorly understood. The classification of PSE is confusing, and there is neither a clear agreement on its incidence and prognosis nor a consensus about specific treatments. The diagnosis of PSE requires the occurrence of late seizures: epileptic events occurring 1 week or more after an ischemic stroke. Late seizures differ from early seizures by the presence of permanent structural changes in the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Sprouting of the synaptic connections between surviving deafferented neurons and the substantial remodeling of spared areas and pathways are crucial for recovery from brain damage. Nonetheless, post-stroke plasticity can also result in aberrant synaptogenesis [ 24 ]. The maladaptive organization of neuronal networks may suppress the endogenous seizure control system, generate synchronized neuronal circuits, and restrict ASMs from accessing neuronal targets, therefore leading to pharmaco-resistance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sprouting of the synaptic connections between surviving deafferented neurons and the substantial remodeling of spared areas and pathways are crucial for recovery from brain damage. Nonetheless, post-stroke plasticity can also result in aberrant synaptogenesis [ 24 ]. The maladaptive organization of neuronal networks may suppress the endogenous seizure control system, generate synchronized neuronal circuits, and restrict ASMs from accessing neuronal targets, therefore leading to pharmaco-resistance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] Recent studies have revealed thrombin to be the major driving force not only for ES but also for LS by predisposing to maladaptive plasticity. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, injured brain cells release neurotoxic thrombin [ 111 ]. Moreover, thrombin promotes maladaptive synaptic plasticity that may result in seizures [ 89 , 112 ]. Furthermore, thrombin is involved in intracerebral coagulation, as in the remainder of the body [ 113 ].…”
Section: Thrombin In the Central Nervous Systemmentioning
confidence: 99%
“…These factors trigger a positive feedback loop that promotes epilpetogenesis [ 217 ]. Stroke may also precipitate the development of post-stroke epilepsy by generating permanent structural changes from which an epileptic focus arises [ 112 ]. Additionally, thrombin has direct epileptogenic effects.…”
Section: Epilepsymentioning
confidence: 99%